Replication independent formation of extrachromosomal circular DNA in mammalian cell-free system. - Zoya Cohen (Public Library of Science (PLoS), 2009)
Extrachromosomal circular DNA (eccDNA) is a pool of circular double stranded DNA molecules found in all eukaryotic cells and composed of repeated chromosomal sequences. It was proposed to be involved in genomic instability, aging and alternative telomere lengthening. Our study presents novel mammalian cell-free system for eccDNA generation. Using purified protein extract we show that eccDNA formation does not involve de-novo DNA synthesis suggesting that eccDNA is generated through excision of chromosomal sequences. This process is carried out by sequence-independent enzymes as human protein extract can produce mouse-specific eccDNA from high molecular weight mouse DNA, and vice versa. EccDNA production does not depend on ATP, requires residual amounts of Mg(2+) and is enhanced by double strand DNA breaks.